The Role of AIF-1 in the Aldosterone-Induced Vascular Calcification Related to Chronic Kidney Disease: Evidence From Mice Model and Cell Co-Culture Model - Chang, Xueying; Hao, Jianbing; Wang, Xingzhi; Liu, Jingwei; Ni, Jie; Hao, Lirong (Frontiers in Endocrinology, 2022)
Increasing evidence suggests that aldosterone plays an essential role in vascular calcification which is a serious threat of cardiovascular disease (CVD) developed from chronic kidney disease (CKD). However, the exact pathogenesis of vascular calcification is still unclear. In vivo experiments, we established CKD-associated vascular calcification mice model and knockout mice model to investigate the causal relationship between allograft inflammatory factor 1 (AIF-1) and vascular calcification. Endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) co-culture experiment was performed to further explore the mechanisms of calcification. The results of the aldosterone intervention mice model and transgenic mice model showed that aldosterone could cause calcification by increasing the AIF-1 level. The results of in vitro co-culture model of ECs and VSMCs showed that AIF-1 silence in ECs may alleviate aldosterone-induced calcification of VSMCs. In conclusion, our study indicated that aldosterone may induce vascular calcification related to chronic renal failure via the AIF-1 pathway which may provide a potential therapeutic target.